2019
DOI: 10.1115/1.4043612
|View full text |Cite
|
Sign up to set email alerts
|

Well Clean-Up Using a Combined Thermochemical/Chelating Agent Fluids

Abstract: The well clean-up process involves the removal of impermeable filter cake from the formation face. This process is essential to allow the formation fluids to flow from the reservoir to the wellbore. Different types of drilling fluids such as oil- and water-based drilling fluids are used to drill oil and gas wells. These drilling fluids are weighted with different weighting materials such as bentonite, calcium carbonate, and barite. The filter cake that forms on the formation face consists mainly of the drillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Recently, Mahmoud 40 found that using the high temperature and pressure generated using thermochemical fluid (ammonium chloride and sodium nitrate salts) was able to hydrolyze the polymer coat covering the filter cake material. According Mahmoud 40 , the exothermic reaction (Eqs. 2-4) generated temperature and pressure ensured the removal of the polymer coat around the filter cake material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mahmoud 40 found that using the high temperature and pressure generated using thermochemical fluid (ammonium chloride and sodium nitrate salts) was able to hydrolyze the polymer coat covering the filter cake material. According Mahmoud 40 , the exothermic reaction (Eqs. 2-4) generated temperature and pressure ensured the removal of the polymer coat around the filter cake material.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the polymer layer of the filter cake must be dissolved prior to the filter cake washing process 15 , 38 using any of the regular polymer breakers such as α-amylase to degrade this layer 39 . Recently, Mahmoud 40 found that using the high temperature and pressure generated using thermochemical fluid (ammonium chloride and sodium nitrate salts) was able to hydrolyze the polymer coat covering the filter cake material. According Mahmoud 40 , the exothermic reaction (Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Application of thermochemical is widely found in petroleum engineering applications. Recently, Mahmoud [35] used thermochemical to remove a filter cake and provide experimental evidences to clean up the oil and gas wells after drilling operations. Hassan et al [36] presented a new technique to remove condensate banking by using thermochemical.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Barite has very low solubility in mineral and organic acids, compared to other weighting materials in drilling fluids. Barite also has moderate solubility in high pH chelating agents such as EDTA and DTPA [ 23 ]. The filter cake can be removed through either a single-stage or multi-stage process based on the computability of the remover fluid ingredients [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Barite also has moderate solubility in high pH chelating agents such as EDTA and DTPA [ 23 ]. The filter cake can be removed through either a single-stage or multi-stage process based on the computability of the remover fluid ingredients [ 23 ]. This study aims to investigate the removal of barite filter cake and its impact on the breakdown pressure of different rocks.…”
Section: Introductionmentioning
confidence: 99%